Encephalitis caused by human herpesvirus‐6B in pancreas‐after‐kidney transplantation. Issue 5 (21st July 2014) - Yamamoto, T.; Watarai, Y.; Goto, N.; Horikoshi, Y.; Yamada, S.; Yasui, K.; Tsujita, M.; Hiramitsu, T.; Narumi, S.; Katayama, A.; Uchida, K.; Kobayashi, T.
Abstract Human herpesvirus‐6 (HHV‐6) is a common pathogen among children, classically presenting with fever and rash that resolves without specific therapy. HHV‐6 can be reactivated in the immunosuppressed patient. After bone marrow and solid organ transplantation, HHV‐6 has been linked to various clinical syndromes, including undifferentiated febrile illness, encephalitis, myelitis, hepatitis, pneumonitis, and bone marrow suppression. However, HHV‐6 encephalitis after pancreatic transplant has rarely been reported. Early diagnosis and treatment of HHV‐6 encephalitis may be important for affected patients. We report the case of a 53‐year‐old pancreas‐after‐kidney transplant recipient who initially presented with high fever and confusion 3 weeks after operation. We managed to save the patient's life and preserve the pancreas graft function. We also review previously reported cases of HHV‐6B encephalitis in solid organ transplant recipients.